Industrial X-Ray Computed Tomography (Springer International Publishing, 2018)
This book covers all aspects of industrial X-Ray computed tomography (XCT) including history, basics, different instrument architectures, hardware and software, error sources, traceability and calibration, and applications. The book is intended for users and developers of XCT instrumentation and software in both industry and academia, being also suitable for postgraduate students.